Effect of initial airway strategy on time to epinephrine administration in patients with out-of-hospital cardiac arrest. (June 2019) - Lupton, Joshua R.; Schmicker, Robert; Daya, Mohamud R.; Aufderheide, Tom P.; Stephens, Shannon; Le, Nancy; May, Susanne; Puyana, Juan Carlos; Idris, Ahamed; Nichol, Graham; Wang, Henry; Hansen, Matt
Abstract: Introduction: Epinephrine and advanced airway management are commonly used during treatment of out-of-hospital cardiac arrest (OHCA). Recent studies suggest that early but not late administration of epinephrine is associated with improved survival. The purpose of this study was to evaluate the effect of initial airway strategy on timing to the first epinephrine dose in OHCA. Methods: This is a secondary analysis of patients enrolled in the Pragmatic Airway Resuscitation Trial who had an advanced airway attempted. We examined differences in time to epinephrine administration by randomly assigned airway strategy, laryngeal tube (LT) or endotracheal tube (ETI); by the duration of airway attempt; and by number of attempts. We used survival methods to account for interval censoring due to unknown administration time. We also examined the association of epinephrine administration timing with survival to hospital discharge. Results: Among 2652 subjects (1299 ETI and 1353 LT), 2579 received epinephrine.There were no significant differences between ETI and LT in median time to initial epinephrine administration (min) (ETI – 9.0 vs. LT – 8.6, p = 0.55). There was no significant association between the duration of airway attempt or number of attempts and time to initial epinephrine administration (p = 0.12 and 0.66, respectively). Early administration of epinephrine (<10 min from EMS arrival) was significantly associated with survival compared to administration ≥10 min (OR 1.36, 95% CI: 1.05, 1.77). Conclusions: There was no significant association between airway strategy and time to initial epinephrine administration. Earlier administration of epinephrine (< 10 min from EMS arrival) was associated with improved survival.